2015
DOI: 10.1111/1440-1681.12507
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of exercise performance by physical training is related to increased hypothalamic neuronal activation

Abstract: The effects of physical training on hypothalamic activation after exercise and their relationship with heat dissipation were investigated. Following 8 weeks of physical training, trained (TR, n = 9) and untrained (UN, n = 8) Wistar rats were submitted to a regimen of incremental running until fatigue while body and tail temperatures were recorded. After exercise, hypothalamic c-Fos immunohistochemistry analysis was performed. The workload, body-heating rate, heat storage and body temperature threshold for cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
(116 reference statements)
1
6
1
Order By: Relevance
“…This is in agreement with previous observations that the highest level of c-fos protein in the SCN is found during the late night while little difference (if any) is observed between ZT2 and ZT16 (Edelstein et al, 2000 ). Furthermore, previous work (Soya et al, 2007 ; Lima et al, 2014a ; Santiago et al, 2016 ) showed that c-fos neuronal activation can detect strong changes in workload (~40–60%), however the present study showed a significant but less pronounced change (~20%). This might reflect a limitation of immunohistochemistry sensitivity that impairs the detection capacity for dynamic processes.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This is in agreement with previous observations that the highest level of c-fos protein in the SCN is found during the late night while little difference (if any) is observed between ZT2 and ZT16 (Edelstein et al, 2000 ). Furthermore, previous work (Soya et al, 2007 ; Lima et al, 2014a ; Santiago et al, 2016 ) showed that c-fos neuronal activation can detect strong changes in workload (~40–60%), however the present study showed a significant but less pronounced change (~20%). This might reflect a limitation of immunohistochemistry sensitivity that impairs the detection capacity for dynamic processes.…”
Section: Discussioncontrasting
confidence: 75%
“…The resting protocol consisted of staying on the treadmill for 90 min. During the second experimental session 90 min after fatigue (Lima et al, 2014b ; Santiago et al, 2016 ; for a short review of c-fos protein expression, please refer to Kovàcs, 1998 ), animals were deeply anesthetized with ketamine and xylazine and were transcardially perfused with 40 mL of heparinized 0.01 M phosphate-buffered saline (PBS), followed by 400 mL of 4% paraformaldehyde (PFA) in 0.2 M phosphate-buffered saline (pH 7.4). The brains were removed for subsequent immunohistochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, the same effect was observed in UN rats, suggesting that all three protocols, including passive heat exposure, have induced this adaptation, which was also reported in heat-acclimated humans [8][9][10]. Lower resting abdominal temperatures have also been observed in rats subjected to an 8-week aerobic training regime consisting of constant-speed sessions performed at 23˚C [36]. However, the existence of lower resting T COL in heat-acclimated rats should be analysed with caution, considering that rats were quickly manipulated to insert the colonic thermistor and attach the tail-skin thermocouple before placement on the treadmill.…”
Section: Figsupporting
confidence: 69%
“…In contrast, our findings disagree with the previous observations made by Santiago et al [36], who observed an increased tail heat loss during exercise following an 8-week aerobic training consisting of constant-speed sessions. In the latter study [36], all training and testing were performed in a temperate environment, and training was initiated when rats were very young (i.e., 4 weeks old); these differences in methods may explain the different results yielded by the two studies. Particularly, dry heat exchange through the tail is dependent on cutaneous vasodilation that favours convection, which is more relevant in temperate than in hot environments due to a greater thermal gradient between the skin and surroundings under the former conditions.…”
Section: Figmentioning
confidence: 99%
“…The training protocols consisted of running sessions on a treadmill across 8 weeks, with 5 weekly sessions always performed at the same time of day. The three protocols used in this study are described in detail in the Supporting Information section of the manuscript ( S1 – S3 Tables) and were adapted from a protocol proposed by Santiago et al [ 18 ]. At the last session of the aerobic training protocols, the increase in speed relative to the first session corresponded to 225% (INT), 125% (ID) and 38.5% (DUR; Fig 1A ), whereas the increase in duration corresponded to 38.5%, 100% and 225% in the INT, ID and DUR groups, respectively ( Fig 1B ).…”
Section: Methodsmentioning
confidence: 99%